1985
DOI: 10.1159/000183489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorpromazine on Peritoneal Clearances

Abstract: Chlorpromazine added to the dialysate improved the ultrafiltration and increased peritoneal clearances of urea and inulin. These results were postulated to be due to the narrowed stagnant dialysate fluid layer by the surface-active property of chlorpromazine. The study suggested another way to improve large solute (possibly uremic toxin) transport by using substances that facilitate convective transport. Intraperitoneal chlorpromazine increased the peritoneal dialysis efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…It should be noted that Indraprasit and Sooksriwongest [9] also obtained clearances which were higher than those of controls by using chlorpromazine peritoneally and this increase was attributed to greater liquid trans port (convection).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It should be noted that Indraprasit and Sooksriwongest [9] also obtained clearances which were higher than those of controls by using chlorpromazine peritoneally and this increase was attributed to greater liquid trans port (convection).…”
Section: Discussionmentioning
confidence: 90%
“…ysis without modifying the osmotic power of the solution. The first report by Indraprasit and Sooksriwongest [9] cam out in 1985: a study on the kinetics of peritoneally administered chlorpromazine in patients on CAPD which revealed that this drug caused an increase in ultra filtration and in peritoneal clearances. An accurate inves tigation on its pharmacological action had led to the conclusion that the only possibility was that chlorproma zine would act by lowring superficial tension, hence its effect on peritoneal transport.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylcholine [14] and chlorpromazine [15] have also been shown to increase measured ultrafiltra tion and solute clearances without increasing the osmotic pressure of the dialysis solution or changing peritoneal permeability times area. With these drugs it was con cluded that the increase in dialysate drain volumes re sulted from a reduction in surface tension, a decrease in the thickness of the stagnant fluid film over the mésothél ium and consequently an increase in water and solute transperitoneal transport.…”
Section: Discussionmentioning
confidence: 99%
“…P reservation of ultrafiltration (UF) volume is a major concern in maintaining long-term continuous ambulatory peritoneal dialysis (CAPD), since loss of UF volume is the main reason for patient dropout. Several pharmacological agents have proven to be effective in enhancing solute transport and water transport (1)(2)(3)(4)(5)(6)(7)(8)(9). However, they have not been used in clinical practice because their clinical usefulness has not yet been established.…”
Section: ♦ ♦ ♦ ♦ ♦ Conclusionmentioning
confidence: 99%